2013
DOI: 10.5455/vetworld.2013.541-545
|View full text |Cite
|
Sign up to set email alerts
|

Study on isolation, molecular detection of virulence gene and antibiotic sensitivity pattern of Escherichia coli isolated from milk and milk products

Abstract: Aim: The study was undertaken to isolate pathogenic E. coli from milk and various milk products, detection of virulence gene using Polymerase chain reaction (PCR) and investigate their antibiotic sensitivity pattern. Materials and Methods: Altogether 250 milk and various milk products samples consisting of raw milk (50), cheese (50), ice-cream (50), mawa (50) and dahi (50) were collected from milk vendors, retail shops located in Anand city, under aseptic precautions. For the enrichment of the organism from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 2 publications
3
12
2
Order By: Relevance
“…Studies conducted on milk have revealed current findings are in disagreement with some other previous studies who have reported higher frequency of stx2 than stx1 31 . Studies conducted on bulk milk samples revealed 91% stx2, 8% stx1 and 41% of both stx1 and stx2 genes 4 .…”
Section: Resultscontrasting
confidence: 56%
“…Studies conducted on milk have revealed current findings are in disagreement with some other previous studies who have reported higher frequency of stx2 than stx1 31 . Studies conducted on bulk milk samples revealed 91% stx2, 8% stx1 and 41% of both stx1 and stx2 genes 4 .…”
Section: Resultscontrasting
confidence: 56%
“…Lower results were mentioned by Kumar and Prasad (2010) who found that the highest contamination was recorded in milk from vendors (26%) followed by dairy farm (20%). In addition, lower results were reported by Bali et al, (2013) (32.5%), Rashid et al, (2013) (33.96%), Virpari et al, (2013) High incidences of E. coli in the examined raw milk samples indicated neglected sanitary control in handling of milk and possibly fecal contamination. Microorganisms may gain entry into raw milk from the dairy animals experiencing subclinical or clinical mastitis, or from fecal contamination, particularly around the teats, and from the farm environment particularly the water source and utensils used for the storage of milk on the farm or during transportation (Ombarak and Elbagory, 2015).…”
Section: Resultscontrasting
confidence: 38%
“…Colifrom counts of raw bulk tank milk should be routinely performed to identify the hygienic status under which milk is produced and handled and sanitary status of udder and milking machines (Boor et al, 1998). Results in Table (2) showed the incidence of E. coli in the samples comprising of BTM was (12.5%), (25%) and (12.5%), higher incidence of E. coli (52%) was observed by Virpari et al (2013) and in Soomro et al (2002) 57%, while nearly similar results (26.4%) was reported by Bandyopadhyay et al (2011) and (30.2%) by Farzan et al (2012) lower incidence rate 2.4% was reported by Jayarao et al (2006).…”
Section: Discussionmentioning
confidence: 99%